Peran Blockchain terhadap Lembaga Zakat bagi Pertumbuhan Perekonomian Suatu Negara - Ibnu Habib Wahyudi; Tata Felina Yolanda; Fanny Asyifa Br Lumban Tobing (VISA: Journal of Vision and Ideas, 2023)
Digitalization is a new phenomenon at the beginning of the 21st century, which combines technology and civilization and sets a good example for the ummah, namely through smart and precise methods. It is time for the introduction of the blockchain method at zakat institutions to be a solution to Islamic problems such as the collection and distribution of zakat financing. The purpose of this study is to provide an example of the possibility, opportunity and capability of implementing the blockchain method in zakat institutions, especially in Indonesia. The integration of blockchain into the economic and monetary system creates lucrative opportunities, conversely, blockchain can pose a threat to the economic and monetary system. The purpose of this research is to find out the impact of the blockchain. This research method is a literature study that examines the literature on various topics and balances it with studies of phenomena from various countries. through dynamic technological advances, especially with the emergence of blockchain technology. Based on the results and research findings, it can be said that blockchain has both positive and negative effects. The positive effects of blockchain on the functioning of the monetary system are the convenience, security and stability of the financial system, which can affect economic growth, while the negative effects of blockchain change the system/policy that previously occurred to be decentralized. and losses mainly from government agencies. Through the advancement of Dynamism technology, especially emerging blockchain technology, the zakat environment will be more efficient for blockchain providing a sustainable, timely, secure and open data decentralization method. Various issues that can be suggested to advance this practice include increasing the staffing capacity of zakat institutions, increasing awareness of zakat obligations as well as examples of digitizing zakat, collaboration between Opz and collaboration with various platforms. Keywords: Blockchain, Zakat, State Economy